Borrowings spelling reforms of English: Borrowings spelling reforms of English - Alibekova, Zilola (Журнал иностранных языков и лингвистики, 2021)
This article is showed different ways, types of pronunciation are classified in every language differentiating the quantity of main sounds, phonemes. Sounds make phonemes according to their functional generality.